Institutional Readiness for Inclusive Carbon Market Development in Indonesia - Harifuddin; Darhamsyah; Demmalino, Eymal Bahsar; Salahuddin, Melvin (Journal of Cultural Analysis and Social Change, 2025)
This study explores Indonesia’s institutional readiness to develop an inclusive carbon market as a strategic instrument for achieving sustainable development. Using a qualitative descriptive approach and content analysis of national regulations, international best practices, and academic literature, the research examines how carbon schemes—ranging from emissions trading systems and carbon taxes to result-based payments and REDD+—can integrate environmental, economic, and social dimensions. The findings show that while Indonesia holds substantial potential in forestry and land-use sectors to generate carbon credits and attract green investments, institutional gaps remain in regulatory coherence, technical capacity, monitoring and verification systems, and equitable benefit-sharing mechanisms. Evidence from global experiences underscores that successful carbon markets require transparent governance, cross-sectoral coordination, and strong community participation to prevent social inequities and conflicts over land rights. The study highlights that strengthening institutional capacity and embedding inclusivity into policy design are critical for transforming carbon markets from a purely emission-reduction tool into a catalyst for local empowerment and green economic transformation. These findings provide actionable insights for policymakers seeking to balance climate mitigation, economic growth, and social equity in Indonesia’s pathway toward a low-carbon future.